Modifikasi Cutter Carrier Menggunakan Motor Servo dengan Kendali PLC untuk Menurunkan Cycle Time Mesin Bias Cutter - Eka Samsul Ma'arif; M. Afif Assidiq; Husnibes Muchtar (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2022)
PT. SRI is a motorcycle tire manufacturer whose production machine is Bias Cutter. This machine serves to cut tire cord with a certain size transversely using a cutter carrier. The machine has a problem with bumps and over cutting due to the acceleration and brake functions of the cutter driving motor not working properly. This problem makes it difficult to reduce the cycle time of this machine in order to increase daily productivity. Modifications were made by replacing the motor that previously used a single-phase induction motor into a servo motor as a cutter carrier driver and adding a Programmable Logic Controller (PLC) as a pulse generator which has a special role in adjusting the linear position, speed, and braking of the servo motor. This modification contributes to reducing the cycle time of the cutting process from 3.8 seconds to 3.0 seconds and increasing the production capability of tire cord from 20,432 pcs/day to 24,899 pcs/day.